The minimum wage in a deflationary economy: The Japanese experience, 1994 - 2003 - Ryo Kambayashi; Daiji Kawaguchi; Ken Yamada (Institute for the Study of Labor (IZA), 2010)
The statutory minimum wage has steadily increased for decades in Japan, while the median wage has fallen nominally since 1999 because of a severe recession. We use large micro-data sets from two government surveys to investigate how the minimum wage has affected the wage distribution under unusual circumstances of deflation. The compression of the lower tail of the female wage distribution is largely explained by an increased real value of the minimum wage. Steady increases in the effective minimum wage reduced employment among low-skilled, middle-aged female workers, but the mechanical effect associated with disemployment on wage compression was minimal.
Keywords: J23; J31; J38; 330; Minimum wage; wage distribution; wage inequality; employment; deflation; Mindestlohn; Deflation; Lohnstruktur; Beschäftigungseffekt; Frauenerwerbstätigkeit; Japan